ENERGY RENOVATION OF AN OLDER HOUSE - Praunseis, Zdravko; Avsec, Jurij; Simon Marčič, Simon Marčič; Strojko, Renato (Journal of Energy Technology, 2024)
This paper presents an energy renovation of an older house, according to state regulations for efficient energy use. There are many ways to design successful energy efficient homes, because they can be built from many different types of material. Becoming a successful builder of energy-efficient homes does not merely require proficient knowledge of theory in new building techniques, but also skills in implementing innovative designs and high-quality construction practises. The energy performance of the building is evaluated and then an energy performance certificate is granted; these certificates are obligatory for all public buildings and also for all buildings that are rented or sold.